2020
DOI: 10.1007/s11482-020-09866-7
|View full text |Cite
|
Sign up to set email alerts
|

Leisure Time Sports Activities and Life Satisfaction: Deeper Insights Based on a Representative Survey from Germany

Abstract: Observational and experimental studies show that leisure time sporting activity (LTSA) is associated with higher well-being. However, scholars often seem to assume that 1) LTSA fosters “general” life satisfaction, thereby ignoring effects on domain satisfaction; 2) the effect of LTSA on well-being is linear and independent of a person’s general activity level; 3) the amount of LTSA is more important than the repertoire of LTSA, i.e. the number of different activities; 4) all kinds of LTSA are equal in their ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 51 publications
2
21
0
5
Order By: Relevance
“…Whereas numerous previous studies have shown that LTSE is beneficial for a variety of quality of life and mental health outcomes (e.g. Wiese et al 2018;Mutz, Reimers and Demetriou 2020), only few accounts addressed the role of LTSE changes and particularly forced LTSE reductions for health and well-being. A handful of experiments with small and non-representative samples indicate that a forced withdrawal of sport and exercise for a short period is detrimental for mental health (Edwards and Loprinzi 2016;Endrighi et al 2016;Blough and Loprinzi 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas numerous previous studies have shown that LTSE is beneficial for a variety of quality of life and mental health outcomes (e.g. Wiese et al 2018;Mutz, Reimers and Demetriou 2020), only few accounts addressed the role of LTSE changes and particularly forced LTSE reductions for health and well-being. A handful of experiments with small and non-representative samples indicate that a forced withdrawal of sport and exercise for a short period is detrimental for mental health (Edwards and Loprinzi 2016;Endrighi et al 2016;Blough and Loprinzi 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A possible remedy for pandemic-related strains and frustrations is sport and exercise. Beyond their general benefits for various aspects of physical health (Rhodes, Janssen, Bredin, Warburton, & Bauman, 2017 ), sport and exercise activities are also associated with positive mood and high levels of life satisfaction (Dolan, Kavetsos, & Vlaev, 2014 ; Mutz, Reimers, & Demetriou, 2020 ). Scholars also regard a regular involvement in sports as a buffer of stress, facilitator for coping and source of resilience (Gerber & Pühse, 2009 ; Klaperski, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In future studies based on the topic of student-athletes, the researchers could study the types of approaches that can be used by conducting interviews with student-athletes, teachers, and school administrations. Mutz et al (2020) analysed life satisfaction within the frame of leisure time sports activities through a survey conducted on the German young population. The study revealed that sports have a beneficial effect on "well-being".…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%